QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) PAYMENT SYSTEM IMPLEMENTATION IN THE MSME SECTOR IN THE CITY OF PEMATANGSIANTAR - Azhari, Ayunda (Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine first, the knowledge of MSME actors in Pematangsiantar using QRIS. Second, the benefits of using QRIS for MSME actors and the three obstacles for MSME actors in Pematangsiantar city in using QRIS. This type of research uses descriptive qualitative research with data collection methods, namely conducting observations, interviews, documentation and literature studies. The results of the study conclude that firstly, the majority of MSME actors in Pematangsiantar know that QRIS is a digital payment instrument issued by Bank Indonesia. This QRIS provides advantages over other digital payment systems. Second, the existence of QRIS helps merchants MSME to make payments more practical, fast and secure and with the convenience of these transactions, people choose to shop and will indirectly increase income for MSME actors. Third, the internet network is less stable in conducting transactions so that it becomes an obstacle for MSME actors and also consumers in conducting transactions. And the existence of a merchant discount rate (Mdr) fee of 0.07% which is applied to traders is an obstacle for MSME actors in Pematangsiantar.Bank Indonesia.“Setelah Bunga AcuanTurun, Masih Ribetdengan Banyak QR Code?,” dalamMajalah Bank Indonesia Bicara, 2019.BI dan LPPI.Profil Bisnis Usaha Mikro, Kecil dan Menegah (UMKM). Jakarta: Bank Indonesia, 2015.Direktorat Akunting dan Sistem Pembayaran dan Direktorat Pengedaran Uang. Laporan Sistem Pembayaran dan Pengedaran Uang. Bank Indonesia, 2008.Hendarsyah, D. (n.d) .Penggunaan Uang Elektronik dan Uang Virtual Sebagai Pengganti Uang Tunai di IndonesiaHarahap, Isnaini. Ekonomi Pembangunan: Pendekatan Transdisipliner. Medan : FEBI UIN-SU Press,2015.Harahap,Muhammad Ikhsan.Implementasi Produk Wakaf Uang Melalui Lembaga Keuangan Syariah. [Laporan Penelitian] UIN SUMUT, 2020.Imrawan Ady dkk. Analisis Peluang Usaha di Kota Pematangsiantar Menghadapi Destinasi Wisata Danau Toba, e-jurnal binawakarya, Vol.15 No 1, 2021.Pohan, Aulia. Sistem Pembayaran (Strategi dan Implementasi di Indonesia), Jakarta: Rajawali Pers, cet 2, 2013.Rahmani, Nur Rahmadi Bi.Meteodologi Penelitian Ekonomi.Medan: Febi UIN-SU Press, 2016.https://www.bi.go.id